2011
DOI: 10.1158/1940-6207.capr-10-0220
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Maternal Exposure to Cow's Milk High or Low in Isoflavones on Carcinogen-Induced Mammary Tumorigenesis among Rat Offspring

Abstract: We investigated whether maternal exposure during pregnancy to cow's milk containing endogenous estrogens and insulin-like growth factor 1 (IGF-1) and either high or low levels of isoflavones from dietary legumes (HIM and LIM, respectively) affected carcinogen-induced mammary carcinogenesis in female rat offspring. Pregnant Sprague-Dawley rats were given HIM, LIM, or tap water (control) from gestational day (GD) 11 until birth; hereafter all rats received tap water. Mammary tumorigenesis was induced by administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 49 publications
(68 reference statements)
0
6
0
2
Order By: Relevance
“…However, interpretation of specific macronutrient effects is very difficult due to the widely varied macronutrient sources across the added foods and the dietary interaction across the varied fat, protein, and carbohydrate backgrounds. Further, there is some evidence that specific components utilised in the cafeteria diet may have deleterious effects such as those related to dairy intake in the rodent [34, 35] and oxidative stress [36]. Recent work by Sampey et al investigated the obesogenic and inflammatory consequences of a cafeteria diet compared to a lard-based 45% (of calories) HF diet in the rodent.…”
Section: Animal Models Of Maternal Obesitymentioning
confidence: 99%
“…However, interpretation of specific macronutrient effects is very difficult due to the widely varied macronutrient sources across the added foods and the dietary interaction across the varied fat, protein, and carbohydrate backgrounds. Further, there is some evidence that specific components utilised in the cafeteria diet may have deleterious effects such as those related to dairy intake in the rodent [34, 35] and oxidative stress [36]. Recent work by Sampey et al investigated the obesogenic and inflammatory consequences of a cafeteria diet compared to a lard-based 45% (of calories) HF diet in the rodent.…”
Section: Animal Models Of Maternal Obesitymentioning
confidence: 99%
“…hydrolysis (0.2 mL sulfatase/glucuronidase from H. pomatia , 52 °C, and 2 h) - Centrifugation - SPE (C18) - Evaporation to dryness - Reconstitution in MeOH (80%, v / v ) - Filtration (0.45 μm) Flachowsky et al ( 2011 ) BA, DA, EQ, FO, and GL ( feeding experiments and health impact experiments ) Frozen (−20 °C) - Equilibration at room temperature - Enz. hydrolysis (β-glucuronidase, 100 μL.4 mL −1 of milk, 37 °C, and 1 h) - Centrifugation (cream and precipitate were discarded) - Double L/L extraction (hexane and ethyl acetate, 3 × 3 mL) - Evaporation to dryness - Re-suspension (0.5 mL acetonitrile) - Filtration (0.2 μm) Nielsen et al ( 2011 ), Skaanild and Nielsen ( 2010 ), Nielsen et al ( 2009 ) and Andersen et al ( 2009b ) DA, EQ, GE, and GL ( technological processing and feeding experiments ) Frozen (−20 °C) - Enz. hydrolysis (100 μL β-glucuronidase [11,400 U.mL −1 ]/ sulfatase [3200 U.mL −1 ] from H. pomatia type H2 were added at 2 mL of milk and 3 mL of acetate buffer [0.1 M and pH 5], 37 °C, and 12 h) - L/L extraction (3 × 2 mL ethylacetate) - Centrifugation - Evaporation to dryness - Reconstitution (0.5 mL methanol:water [1:1, v / v ]) Křížová et al ( 2011a ), Křížová et al ( 2011b ), Krajčová et al ( 2010 ), and Třináctý et al ( 2009 ) BA, DA, EQ, FO, GE, and GL ( commercial milks ) N.C. - L/L extraction (10 mL milk/10 mL acetone/acetate buffer [2 M, pH 5.2, 9:1, v / v ]) - Enz.…”
Section: Introductionmentioning
confidence: 99%
“…The total levels of phyto-oestrogens that can be achieved in cows' milk through specific feeding practices are relatively low compared with the 200-6500 mg/l that can be measured in soy milk and other soy-based beverages (Kano et al 2006;Dip et al 2008). However, the relatively low concentrations of phyto-oestrogens in milk do not rule out any biological effects of milk phyto-oestrogens, as previous in-vitro and in-vivo studies have already shown (Nielsen et al 2009(Nielsen et al , 2011. Owing to the large differences in milk phyto-oestrogen content following the B1 feeding and the two red clover silage based diets (R1 and R2) in the present study, we hypothesized that there would be differences in the proliferative activity of whey in the assays applied.…”
Section: Discussionmentioning
confidence: 93%